Design and analysis of a new hash function gear - Alshaikhli, Imad Fakhri Taha; Alahmad, Mohammad (2014)
A hash function usually has two main components: a compression function or permutation function and mode of operation. In this paper, we propose a new concrete novel design of a permutation based hash functions called Gear. It is a hash function based on block cipher in Davies-Meyer mode. It uses the patched version of Merkle-Damgård, i.e. the wide pipe construction as its mode of operation. Thus, the intermediate chaining value has at least twice larger length than the output hash. Also, we analyze Gear and prove it is hard to attack it with complexities significantly less than brute force and it resists all the generic attacks. And the permutations functions used in Gear are inspired from the SHA-3 finalist Grøstl hash function which is originally inspired from Rijndael design (AES). As a consequence there is a very strong confusion and diffusion in Gear.